Mapping Gender Awareness in English Language Teaching: A Mixed-Methods Study in Indonesian Islamic Universities - Anita, Anita; Haryanto, Nur (IAIN KENDARI, 2026)
This study examines gender awareness in English Language Teaching (ELT) within Indonesian Islamic Higher Education Institutions (PTKI), with a specific focus on three dimensions of gender awareness: attitudes toward gender equality, gender-responsive teaching practices, and gender representation in learning materials. Using a mixed-methods design, the research involved survey responses from 312 students and 54 lecturers, complemented by semi-structured interviews and classroom observations across three Islamic Higher Education Institutions. Quantitative findings show that students report slightly higher gender awareness than lecturers, whereas lecturers perceive gender as having a stronger structural impact on learning processes. Qualitative results further contextualize these differences by identifying four key themes: the creation of inclusive learning environments, increased student motivation and engagement, concerns over gender representation in ELT materials, and the importance of gender-focused professional development for lecturers. Together, these integrated findings demonstrate that gender awareness influences both classroom dynamics and pedagogical decision-making. The study highlights the need for Islamic Higher Education Institutions to embed gender-responsive approaches into curriculum design, teacher training programs, and institutional policies to promote inclusivity and enhance learning outcomes in ELT.